1998
DOI: 10.1089/dna.1998.17.603
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning and Characterization of a Tumor Rejection Antigen from Rat Histiocytoma, AK-5

Abstract: We have cloned and sequenced a tumor rejection antigen from a highly immunogenic rat histiocytoma, AK-5. Recombinant antigen induced an antibody response in syngeneic hosts, and the immunized animals showed significant resistance to AK-5 tumor challenge, where growth of the tumor was retarded. Autologous anti-AK-5 antibody, as well as the specific monoclonal antibodies raised against whole AK-5 cells, recognized the recombinant protein. Similarly, recombinant antigen was able to neutralize antitumor antibody i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2002
2002
2005
2005

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…(39) A partial sequence of coronin 7 has been previously identified as a histiocytoma-specific p70 antigen strongly expressed in the rat thymus, spleen and brain. (40) This expression pattern is consistent with our data on full-length coronin 7 (crn7). (39) We showed that, in contrast to cytosolic coronin 3, cytosolic crn7 is not phosphorylated, while the membrane-associated pool is phosphorylated on tyrosine residues suggesting that crn7 is recruited from the cytosol to Golgi membranes upon tyrosine phosphorylation.…”
Section: Mammalian Coronin 7 Has No Cytoskeleton-related Functions Busupporting
confidence: 92%
“…(39) A partial sequence of coronin 7 has been previously identified as a histiocytoma-specific p70 antigen strongly expressed in the rat thymus, spleen and brain. (40) This expression pattern is consistent with our data on full-length coronin 7 (crn7). (39) We showed that, in contrast to cytosolic coronin 3, cytosolic crn7 is not phosphorylated, while the membrane-associated pool is phosphorylated on tyrosine residues suggesting that crn7 is recruited from the cytosol to Golgi membranes upon tyrosine phosphorylation.…”
Section: Mammalian Coronin 7 Has No Cytoskeleton-related Functions Busupporting
confidence: 92%
“…The AK-5 tumor shows a particular growth pattern when transplanted subcutaneously. The tumor grows rapidly during the growth phase (days 1-14), after which necrotic spots appear and the tumor undergoes rejection (days 15-25) followed by the healing phase (days [25][26][27][28][29][30][31][32][33][34][35] when the wound heals and the animals become totally normal and are immunized against AK-5 tumor (7).…”
Section: Cellular Influx Into the Peritoneal Compartmentmentioning
confidence: 99%
“…The coiled-coil domain of p57/coronin-1 includes a so-called leucine zipper motif, with four leucine residues that appear every seven amino acid residues [6]. Because the leucine zipper motif is not found in other mammalian coronin members [16,[20][21][22][23][24], we reasoned that it may serve a function unique to p57/coronin-1, and tested the hypothesis that the leucine zipper motif mediates homodimer formation.…”
Section: Introductionmentioning
confidence: 99%